A doubtful and perilous experiment : advisory opinions, state constitutions, and judicial supremacy - Topf, Mel A. (New York : Oxford University Press, 2011)
The story of attempts to defend advisory authority, including several attempts to amend the U.S. Constitution to require the Supreme Court to issues them. It tells the story also of the uneasy relation between advisory opinions and judicial review as well as the expansion of judicial power.
Includes bibliographical references and index.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 21, 2012).
Keywords: Advisory opinions -- United States -- States; Judicial review -- United States -- States; Constitutional law -- United States -- States